Creative Economy on the Wellness Tourism of Elderly Tourists in Thailand: A Comparative Study of Thai, Japanese, and Chinese - Keadplang, Kittiya; Hansuk, Witsanu; Suchaoin, Punyawee; Pimanmassuriya, Khanitha (Rajapark Journal, 2024)
This study illuminates the crucial role of the creative economy in shaping the wellness tourism preferences and experiences of elderly tourists in Thailand, Japan, and China. By uncovering valuable insights, it provides guidance for tourism stakeholders, policymakers, and marketers aiming to enrich the appeal and sustainability of wellness destinations. The findings suggest promising opportunities for crafting tailored wellness offerings that resonate with each country’s unique cultural and generational dynamics, ultimately fostering economic growth and enhancing well-being among the elderly population in these regions. In essence, the analysis underscores the profound impact of the creative economy theory on wellness tourism in these nations. Leveraging their rich cultural heritage and innovative capabilities, these countries have strategically bolstered the wellness tourism sector, particularly for elderly travelers. This symbiotic relationship between culture, creativity, and economic growth has spurred the development of tailored wellness experiences, catering to the diverse needs of elderly tourists and solidifying these countries' positions as premier wellness destinations. The integration of creative economy principles into wellness initiatives not only enhances the quality of experiences but also fosters authenticity and cultural immersion, setting these destinations apart in a competitive market. As the global population ages, the convergence of wellness tourism and the creative economy presents significant potential for driving sustainable tourism sector development while addressing the evolving needs of elderly travelers. Hence, policymakers and industry stakeholders must prioritize the preservation and promotion of cultural heritage, innovation, and authenticity to ensure the continued growth and success of wellness tourism in these culturally diverse nations.